Analisis Persepsi Stakeholder dalam Penanganan Risiko Pestisida sebagai Dasar Penyusunan Policy Brief di Kabupaten Brebes - Sri Lestari; Hanifa Maher Denny; Yuliani Setyaningsih (Pro Health Jurnal Ilmiah Kesehatan, 2020)
The use of pesticides that are not completely on target creates residues and has a negative impact on health and the environment. The lack of guidance from stakeholders and the lack of knowledge about the dangers of pesticides cause farmers to ignore the risks of excessive use of pesticides. Preventive efforts are needed to reduce the impact of pesticide use, so that the policy brief could be Â prepared as an effort to minimize the impact of pesticide use through more effective policy recommendations that is to be addressed to local governments and related agencies. This research used a qualitative approach. The sample in this study consisting of the community health centre officers, the Health Service and the Agriculture Service. Stakeholder perceptions in policy making were influenced by knowledge factors, family background factors and need factors. The policy brief was prepared based on the results of interviews and focus group discussions with informants relating to the impact of and the prevention of the use of pesticides excessive. The stages of preparing a policy brief start from determining the problem and audience, creating a policy framework, writing an executive summary and reviewing the results of the policy brief. Perception stakeholders for developing the use of pesticides to have not run optimally even though we already be a job and the program as a clear. The need for monitoring and evaluation counseling and flanking by stakeholders to farmers periodically 6 months.